2011
DOI: 10.1007/s00586-011-1831-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo preclinical evaluation of the influence of osteoporosis on the anchorage of different pedicle screw designs

Abstract: We investigate the anchorage of pedicle screws with different surface treatments in osteoporotic bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Ovatectomized animals had significantly lower local bone density than fake animals. Osteointegration and bone-graft contact rates were found to be significantly lower in osteoporotic animals 19 .…”
Section: Experimental Studiesmentioning
confidence: 84%
“…Ovatectomized animals had significantly lower local bone density than fake animals. Osteointegration and bone-graft contact rates were found to be significantly lower in osteoporotic animals 19 .…”
Section: Experimental Studiesmentioning
confidence: 84%
“…9,10 As studies have found strong correlation between BMD and pullout strength of pedicle screws, osteoporotic patients who are undergoing posterior instrumentation is at high risk of screw loosening and nonunion which may lead to unsatisfactory clinical outcome. 10,28 In addition, as osteoporosis worsens, cortical bone thickness at the pedicle also decreases, which results in the weakening of pedicle screw fixation strength. 10,28 In addition, as osteoporosis worsens, cortical bone thickness at the pedicle also decreases, which results in the weakening of pedicle screw fixation strength.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is usually caused by several factors related to genetics, aging, hormone levels, drug assumption, malabsorption or chronic kidney disease, and harmful lifestyles (e.g., smoking and alcoholism) (Giavaresi et al 2011). Among them, the most common cause, in women, is estrogen deficiency, which not only leads to bone weakness, increased fracture risk, and implant failure (Kim et al 2012), but also "fragility syndrome," with manifestations and implications also on soft tissues (Torricelli et al 2012;Calleja-Agius and Brincat 2009).…”
Section: Introductionmentioning
confidence: 99%